DEVELOPMENT OF A MANUALLY OPERATED RICE TRANSPLANTER USING FOUR-BAR LINKAGE MECHANISM - RANJAN KUMAR NIRALA and UTTAM KUMAR* (The Journal of Research ANGRAU, 2020)
The manually operated two-row rice transplanter was developed to transplant root washed type seedlingsusing four bar linkage transplanting mechanism during 2016. Effective field capacity of the transplanter was0.012 ha h-1 at an operating speed of 0.36 km h-1. The average height of the seedlings were 162.2 mm, 190.35mm and 220.55 mm for 20, 25 and 30 days old seedlings, respectively.Average hill-to-hill spacing, number ofseedlings per hill and depth of planting were 200.22 mm, 4.06 mm and 61.66 mm, respectively. Average missinghills, floating hills and visible damage of the transplanter were10.33%, 6.17% and 2.83%, respectively.Cost oftransplanting by the transplanter was Rs.6500 ha-1, whereas, by manual transplanting it was Rs.11400 ha-1,thus,there is a saving of Rs.4900 ha-1.